INFLUENCE OF TARGET SEEDING RATES BASED ON THOUSAND KERNEL WEIGHT ON VEGETATIVE GROWTH TRAITS OF TRITICALE, VARIETY ADMIRAL- Part I. - Sumaya A. Abdullah; Ahmed S. Khalaf (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A field experiment was conducted during two seasons 2019-2020 and 2020-2021 at the Grdarasha Research Station of the Agricultural Engineering Sciences College-Salahaddin University-Erbil. The experiment was designed as factorial within randomized complete block design (RCBD), with three replicates. The first factor included three target seeding rates of Triticale (×Triticosecale wittmack, variety Admiral (200,250,and300seeds.m-2), while the second factor was three grain size grades whole, thousand kernels weight (TKW) 47.32 g, heavy seeds, TKW 54.04 and light seeds TKW 40.18 g. The results revealed to no significant influence of seeds weight or seeding rates and their interaction on this trait excluding whole sample seed (ungraded) at the rate target of 300 seeds.m-2, which was significantly reduced flag leaf area. Leaf area index was significantly varied among seed weight and target seeding rates or by their interactions. The plant height of triticale although it was higher for heavy seeds and higher target seeding rates, but it was not reached significant level, either by seed grade or target seed rate and their interactions in both. Plant height ranges from 88.00 for heavy seeds at rate 300 seeds.m-2 to 83.00 for light seeds at rate 200 seeds.m-2 for the season 2019-2020. The highest tillers number was recorded for seed rate 300.m-2 with whole ungraded seeds (176.00).